Diesel oil NiMoFe / Al2O3 hydrodesulfurization catalyst and preparation method and application thereof

By using Al2O3 support and NiMoFe catalysts with molybdenum, iron and nickel oxides in diesel hydrodesulfurization catalysts, the molar ratio between Mo and Fe is optimized, and the problems of complex and low efficiency of catalyst preparation in the prior art are solved, and low cost is achieved , efficient diesel desulfurization effect reduces energy consumption and environmental impact.

CN119259065APending Publication Date: 2025-01-07JIANGSU UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411564563.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing diesel hydrodesulfurization catalyst preparation procedures are complex, the reaction conditions are harsh, the cost is high and the desulfurization efficiency is low, resulting in increased production costs of enterprises and environmental pollution.

Method used

The NiMoFe/Al2O3 hydrodesulfurization catalyst with Al2O3 support and molybdenum, iron and nickel oxides as active ingredients is used to optimize the molar ratio of Mo to Fe to improve the activity and stability of the catalyst through improved impregnation and calcining processes.

Benefits of technology

It achieves efficient diesel desulfurization under low-cost and mild conditions, significantly reduces energy consumption and environmental impact, improves the stability and activity of the catalyst, and reduces synthesis costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259065A_ABST
    Figure CN119259065A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of petrochemical industry, and relates to a diesel oil NiMoFe / Al2O3 hydrodesulfurization catalyst and a preparation method and application thereof. The hydrodesulfurization catalyst provided by the invention comprises an Al2O3 carrier and an active component loaded on the Al2O3 carrier, wherein the active component is composed of a molybdenum oxide, an iron oxide and a nickel oxide; the molybdenum oxide is molybdenum trioxide; the oxide of iron is ferric oxide; the nickel oxide is nickel oxide. The preparation process of the catalyst is simple to operate and low in cost, double active phases MoFe are introduced, the structure and morphology of the active phases and the amount of Lewis acid and Bronsted acid on the surface of the carrier are adjusted by changing the molar ratio of Mo to Fe, the hydrogenation activity is improved, and ultra-deep hydrodesulfurization of an oil product can be realized under the condition of low energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of petrochemical industry and relates to a diesel NiMoFe / Al2O3 hydrodesulfurization catalyst and a preparation method and application thereof. Background Art

[0002] With the steady growth of the economy and the strengthening of environmental protection policies, the quality standards of petroleum products are also constantly improving. In recent years, through the implementation of more stringent emission standards, such as China VI and Euro VI, higher requirements have been put forward for the sulfur content in petroleum products. These standards not only limit the emission of pollutants in automobile exhaust, but also promote the upgrading of oil quality. For example, the implementation of the China VI standard requires a significant reduction in the sulfur content of gasoline and diesel for vehicles, thereby reducing the damage to the environment caused by sulfur oxides emitted by diesel engines.

[0003] Chinese patent CN 111298800 A discloses a hydrodesulfurization catalyst and its preparation method and application, wherein heteroatom-modified γ-alumina is used as a carrier, and the active components loaded are Ni and Mo, wherein the active components include 2wt%-8wt% NiO and 10wt%-25wt% MoO3. The hydrodesulfurization catalyst has a liquid hourly space velocity (LHSV) of 5h -1 The maximum removal rate of 4,6-dimethyldibenzothiophene can only be maintained at 87%, the catalytic efficiency is low, and the energy consumption is high. Chinese patent CN 101797513A discloses a catalyst for coke oven gas hydrodesulfurization, which uses γ-Al2O3 as a carrier, loaded with active components and additives, wherein the active components are 2% to 10% iron, 5% to 20% molybdenum and 0.1% to 5% nickel oxides, and the additives are 1% to 8% phosphorus oxides. In the process of preparing the catalyst, molybdenum salts and phosphoric acid, nickel salts, and iron salts are mixed and then loaded onto the γ-Al2O3 carrier by impregnation. The mixed impregnation is used to load the metal salts onto the carrier at the same time, but there will be precipitation when the iron salt and the molybdenum salt are mixed, which may lead to insufficient dissolution, thereby affecting the actual loading of the catalyst to be low and high cost. Chinese patent CN108855116 A discloses a low-load coke oven gas hydrodesulfurization catalyst, which uses γ-Al2O3 as a carrier and loads 0.5% to 1.5% iron, 1% to 3.5% molybdenum and 0.1% to 0.5% nickel. The preparation process of the catalyst also uses mixed impregnation to load the various metal salts onto the carrier at the same time, which may lead to insufficient dissolution, thereby affecting the actual loading of the catalyst to be low and high cost.

[0004] Therefore, how to prepare a catalyst with ultra-deep desulfurization performance to remove sulfides from diesel until it is "sulfur-free" has always been one of the research hotspots and difficulties in the petrochemical field. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the existing fuel desulfurization technology has the problems of complex catalyst preparation procedure, harsh reaction conditions, high processing cost, environmental pollution leading to a substantial increase in enterprise production costs, and low desulfurization efficiency. The present invention aims to provide a catalyst for oil desulfurization with low processing cost and mild conditions that can achieve the purpose of energy conservation and emission reduction, and specifically provides a diesel NiMoFe / Al2O3 hydrodesulfurization catalyst and its preparation method and application.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] The invention discloses a diesel NiMoFe / Al2O3 hydrodesulfurization catalyst, wherein the hydrodesulfurization catalyst comprises an Al2O3 carrier and an active component loaded on the Al2O3 carrier;

[0008] Wherein, the active ingredients are composed of molybdenum oxide, iron oxide and nickel oxide;

[0009] The total mass of the molybdenum oxide and the iron oxide accounts for 8% to 13% of the total mass of the catalyst; the mass of the nickel oxide accounts for 4% of the total mass of the catalyst; the molar ratio of molybdenum to iron is 12 to 144:1;

[0010] The molybdenum oxide is molybdenum trioxide; the iron oxide is ferric oxide; and the nickel oxide is nickel oxide.

[0011] In some embodiments, preferably, the hydrodesulfurization catalyst comprises an Al2O3 carrier and an active ingredient loaded on the Al2O3 carrier; wherein the active ingredient is composed of molybdenum oxide, iron oxide and nickel oxide; the total mass of the molybdenum oxide and the iron oxide accounts for 11% to 13% of the total mass of the catalyst; the mass of the nickel oxide accounts for 4% of the total mass of the catalyst; the molar ratio of molybdenum to iron is 12 to 72:1; the molybdenum oxide is molybdenum trioxide; the iron oxide is ferric oxide; and the nickel oxide is nickel oxide.

[0012] In some embodiments, further preferably, the molar ratio of molybdenum to iron is 24-72:1, and further preferably 36:1.

[0013] Furthermore, the present invention provides a method for preparing the above-mentioned diesel NiMoFe / Al2O3 hydrodesulfurization catalyst, comprising the following steps:

[0014] (1) dissolving triisopropoxyaluminum in a first solvent and stirring, then adding an acid to assist dissolution, then adding a structure directing agent and mixing, then drying and first calcining to obtain a carrier;

[0015] (2) dispersing a molybdenum salt, an iron salt, and a nickel salt in a second solvent to obtain a molybdenum salt dispersion, an iron salt dispersion, and a nickel salt dispersion, respectively;

[0016] (3) impregnating the support obtained in step (1) with a molybdenum salt dispersion, and then drying; then impregnating with an iron salt dispersion, and then drying; and finally impregnating with a nickel salt dispersion, and then drying;

[0017] or,

[0018] The carrier obtained in step (1) is impregnated with an iron salt dispersion, and then dried; then impregnated with a molybdenum salt dispersion, and then dried; and finally impregnated with a nickel salt dispersion, and then dried;

[0019] (4) drying the product obtained in step (3) and performing a second calcination to obtain a NiMoFe / Al2O3 hydrodesulfurization catalyst.

[0020] In some embodiments, in step (1), the first solvent is any one or a combination of ethanol and water; the stirring time is 2 to 6 hours; the acid is any one or a combination of nitric acid, hydroiodic acid, hydrobromic acid, hydrochloric acid and sulfuric acid; the structure directing agent is any one or a combination of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; the mass ratio of triisopropoxy aluminum to the structure directing agent is 2.0 to 2.5:1.

[0021] In some embodiments, preferably, in step (1), the first solvent is ethanol; the stirring time is 4 hours; the acid is nitric acid; the structure directing agent is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; and the mass ratio of the triisopropoxy aluminum to the structure directing agent is 2.0 to 2.1:1.

[0022] The abbreviation of the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is P123; the abbreviation of the polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer is F127.

[0023] Wherein, in step (1), there is no special requirement for the amount of the first solvent, and the raw materials can be evenly dispersed; preferably, the mass volume ratio of the triisopropoxy aluminum to the first solvent is 8.16g:30.0~50.0mL, more preferably 8.16g:35.0~45.0mL, and even more preferably 8.16g:40.0mL.

[0024] Wherein, in step (1), the stirring rate of the stirring is 600 to 1500 rpm, preferably 600 to 1200 rpm, more preferably 600 to 1000 rpm, and even more preferably 800 rpm.

[0025] Wherein, in step (1), there is no special requirement for the amount of the acid used, and the acid can be used to dissolve the undissolved triisopropoxyaluminum.

[0026] Wherein, in step (1), the structure directing agent is in the form of a dispersion, and the solvent is the first solvent. There is no special requirement for the amount of the first solvent in the dispersion, and the raw materials can be evenly dispersed. Preferably, the mass volume ratio of the structure directing agent and the first solvent in the dispersion is 4.0g:15~40mL, more preferably 4.0g:15~30mL, and even more preferably 4.0g:20mL.

[0027] Wherein, in step (1), the drying temperature is 120-140° C., and the drying time is 24-72 h, preferably 24-56 h, more preferably 36-56 h, and even more preferably 48 h.

[0028] In some embodiments, in step (1), the first calcination is performed by raising the temperature from room temperature to 550-560° C. at a heating rate of 1-5° C. / min, and calcining at 550-560° C. for 2-6 hours.

[0029] In some embodiments, preferably, in step (1), the first calcination is to increase the temperature from room temperature to 550-560°C at a heating rate of 1°C / min, and calcine at 550-560°C for 4h.

[0030] In some embodiments, in step (2), the molybdenum salt is ammonium heptamolybdate tetrahydrate; the iron salt is ferric nitrate nonahydrate; the nickel salt is nickel nitrate hexahydrate; and the second solvent is water.

[0031] In some embodiments, in step (2), the ammonium heptamolybdate tetrahydrate is calculated as molybdenum trioxide, the ferric nitrate nonahydrate is calculated as ferric oxide, and the total mass of the molybdenum trioxide and ferric oxide accounts for 8% to 13% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst; the molar ratio of molybdenum in the ammonium heptamolybdate tetrahydrate to iron in the ferric nitrate nonahydrate is 12 to 144:1; the nickel nitrate hexahydrate is calculated as nickel oxide, and the nickel oxide accounts for 4% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst.

[0032] In some embodiments, preferably, in step (2), the ammonium heptamolybdate tetrahydrate is calculated as molybdenum trioxide, the ferric nitrate nonahydrate is calculated as ferric oxide, and the total mass of the molybdenum trioxide and ferric oxide accounts for 11% to 13% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst; the molar ratio of molybdenum in the ammonium heptamolybdate tetrahydrate to iron in the ferric nitrate nonahydrate is 12 to 72:1; the nickel nitrate hexahydrate is calculated as nickel oxide, and the nickel oxide accounts for 4% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst.

[0033] In some embodiments, further preferably, in step (2), the molar ratio of molybdenum in the ammonium heptamolybdate tetrahydrate to iron in the ferric nitrate nonahydrate is 24-72:1, and further preferably 36:1.

[0034] Wherein, in step (2), the ferric nitrate nonahydrate is calculated as ferric oxide, and the mass of the ferric oxide accounts for 0.03% to 0.60% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst.

[0035] In some embodiments, preferably, in step (2), the mass ratio of the ammonium heptamolybdate tetrahydrate to the ferric nitrate nonahydrate, the nickel nitrate hexahydrate, and the carrier is 0.462g-0.498g: 0.007g-0.088g: 0.487g: 3g.

[0036] In some embodiments, preferably, in step (2), the mass volume ratio of the ammonium heptamolybdate tetrahydrate to the ferric nitrate nonahydrate, the nickel nitrate hexahydrate, and the second solvent is 0.462g-0.498g: 0.007g-0.088g: 0.487g: 3mL.

[0037] In some embodiments, in step (3), the mass volume ratio of the carrier to the molybdenum salt dispersion is 1g:1.0~1.2mL; the mass volume ratio of the carrier to the iron salt dispersion is 1g:1.0~1.2mL; the mass volume ratio of the carrier to the nickel salt dispersion is 1g:1.0~1.2mL.

[0038] In some embodiments, preferably, in step (3), the mass volume ratio of the carrier to the molybdenum salt dispersion is 1 g:1.0 mL; the mass volume ratio of the carrier to the iron salt dispersion is 1 g:1.0 mL; the mass volume ratio of the carrier to the nickel salt dispersion is 1 g:1.0 mL.

[0039] In some embodiments, in step (4), the second calcination is performed by raising the temperature from room temperature to 550-560° C. at a heating rate of 1-5° C. / min, and calcining at 550-560° C. for 2-6 hours.

[0040] In some embodiments, preferably, in step (4), the second calcination is performed by raising the temperature from room temperature to 550-560°C at a heating rate of 1°C / min, and calcining at 550-560°C for 4h.

[0041] Wherein, in step (3), the drying is carried out at room temperature, and the drying time is preferably 12 hours.

[0042] Wherein, in step (4), the drying temperature is 120-140° C. and the drying time is 8-36 hours.

[0043] The diesel NiMoFe / Al2O3 hydrodesulfurization catalyst prepared by the above preparation method is also within the protection scope of the present invention.

[0044] The application of the above diesel NiMoFe / Al2O3 hydrodesulfurization catalyst in the desulfurization of petroleum fractions is also within the protection scope of the present invention.

[0045] Specifically, the diesel NiMoFe / Al2O3 hydrodesulfurization catalyst is used as a catalyst to catalyze the hydrodesulfurization reaction of sulfur-containing petroleum fractions; the hydrodesulfurization reaction has a reaction temperature of 340-360°C, a hydrogen partial pressure of 4-6 MPa, and a liquid hourly space velocity of 2.5-100 h -1 , hydrogen-oil volume ratio 200:1.

[0046] Specifically, preferably, the above-mentioned diesel NiMoFe / Al2O3 hydrodesulfurization catalyst is used as a catalyst to catalyze the hydrodesulfurization reaction of sulfur-containing petroleum fractions; the hydrodesulfurization reaction has a reaction temperature of 340°C, a hydrogen partial pressure of 4MPa, and a liquid hourly space velocity of 2.5 to 100h -1 , hydrogen-oil volume ratio 200:1.

[0047] Beneficial effects:

[0048] (1) The preparation process of the catalyst of the present invention is simple to operate and has low cost. By introducing a dual active phase MoFe, the structure and morphology of the active phase and the amount of Lewis acid and Bronsted acid on the carrier surface are adjusted by changing the molar ratio of Mo to Fe, thereby improving the hydrogenation activity. The ultra-deep hydrodesulfurization of oil products can be achieved under low energy consumption conditions, and significant effects are achieved while greatly saving the preparation cost. There is no relevant report on the preparation process of the catalyst of the present invention in the research of hydrodesulfurization in the prior art, and the present invention is original.

[0049] (2) The active component used in the hydrodesulfurization reaction of the present invention is MoFe, which has a strong hydrogenation ability under the dual active components, and its catalytic performance is much higher than the hydrodesulfurization catalysts currently reported.

[0050] (3) Changes in Mo:Fe will affect the interaction between the NiMoFe / Al2O3 catalyst carrier and the active components, thereby improving the hydrogenation activity; the present invention further optimizes and limits Mo:Fe and achieves significant technical effects within the limited range.

[0051] (4) The catalyst provided by the present invention exhibits excellent stability and activity under high flow rate conditions. Compared with the prior art, it can significantly reduce energy consumption while maintaining high performance. This makes the catalyst provided by the present invention more advantageous in industrial applications, not only improving production efficiency, but also reducing the impact on the environment, providing strong support for achieving sustainable development.

[0052] (5) This aspect innovatively upgrades the single molybdenum oxide active component to a dual active component of molybdenum oxide and iron oxide, thereby achieving high activity retention under high flow rate environment. This improvement not only has significant economic advantages and reduces the synthesis cost, but also effectively weakens the metal-support strong interaction (SMSI) through electron transfer, thereby improving the dispersibility of the active component. This improvement in dispersibility further enhances the activity of the catalyst and provides strong support for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0054] Figure 1 This is the XRD spectrum of the NiMoFe / Al2O3 catalyst prepared in Examples 1 to 5 of the present invention.

[0055] Figure 2 The activity diagram of NiMoFe / Al2O3 catalyst prepared in Examples 1 to 5 of the present invention for catalyzing 4,6-DMDBT.

[0056] Figure 3 The hourly space velocity in liquid is 10h -1 The following is the activity diagram of the catalysts prepared in Example 3 and Comparative Examples 1 to 3 for catalyzing 4,6-DMDBT. DETAILED DESCRIPTION

[0057] Various exemplary embodiments of the present invention are described in detail below. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0058] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0059] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the present invention. Other embodiments obtained from the present invention description will be apparent to those skilled in the art.

[0060] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0061] Description: The impregnation experiment used in the present invention is specifically as follows: referring to the impregnation method, the pores in the solid to be impregnated are filled with a liquid reagent to reach a saturated state, and the amount of the liquid reagent at this time is determined.

[0062] The P123 used in the examples of the present invention has a number average molecular weight of 5800.

[0063] Embodiment 1:

[0064] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0065] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0066] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24 The effective substance of Fe(NO3)3·9H2O is MoO3, the effective substance of Fe(NO3)3·9H2O is Fe2O3, and the effective substance of Ni(NO3)2·6H2O is NiO. The total molar amount of Mo and Fe in the catalyst is calculated to be 2.83mmol (i.e. the total mass of MoO3 and Fe2O3 accounts for 12wt% of the catalyst mass), and the mass of NiO accounts for 4wt% of the catalyst mass, where the molar ratio of Mo to Fe is 144:1; the mass of carrier A is 3g. Finally, the required 0.498g (NH4)6Mo7O 24 ·4H2O, 0.007g Fe(NO3)3·9H2O, 0.487g Ni(NO3)2·6H2O.

[0067] 0.498g(NH4)6Mo7O 24 ·4H2O, 0.007g Fe(NO3)3·9H2O, and 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion, ferric nitrate dispersion, and nickel nitrate dispersion, respectively; 3g of carrier A was first impregnated in 3mL of ammonium molybdate dispersion, and dried at room temperature for 12h after impregnation, and then the dried sample was impregnated in 3mL of ferric nitrate dispersion, and dried at room temperature for 12h, and finally the obtained sample was impregnated in 3mL of nickel nitrate dispersion, and dried at room temperature for 12h after impregnation, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst NiMoFe / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed. The order of immersing the support in the ammonium molybdate dispersion and the ferric nitrate dispersion can be changed.

[0068] Embodiment 2:

[0069] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0070] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0071] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24 The effective substance of Fe(NO3)3·9H2O is MoO3, the effective substance of Fe(NO3)3·9H2O is Fe2O3, and the effective substance of Ni(NO3)2·6H2O is NiO. The total molar amount of Mo and Fe in the catalyst is calculated to be 2.83mmol (i.e. the total mass of MoO3 and Fe2O3 accounts for 12wt% of the catalyst mass), and the mass of NiO accounts for 4wt% of the catalyst mass, where the molar ratio of Mo to Fe is 72:1; the mass of carrier A is 3g. Finally, the required 0.494g (NH4)6Mo7O 24 ·4H2O, 0.015g Fe(NO3)3·9H2O, 0.487g Ni(NO3)2·6H2O.

[0072] 0.494g(NH4)6Mo7O 24 ·4H2O, 0.015g Fe(NO3)3·9H2O, and 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion, ferric nitrate dispersion, and nickel nitrate dispersion, respectively; 3g of carrier A was first impregnated in 3mL of ammonium molybdate dispersion, and dried at room temperature for 12h after impregnation, and then the dried sample was impregnated in 3mL of ferric nitrate dispersion, and dried at room temperature for 12h, and finally the obtained sample was impregnated in 3mL of nickel nitrate dispersion, and dried at room temperature for 12h after impregnation, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst NiMoFe / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed. The order of immersing the support in the ammonium molybdate dispersion and the ferric nitrate dispersion may be changed.

[0073] Embodiment 3:

[0074] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0075] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0076] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24 The effective substance of Fe(NO3)3·9H2O is MoO3, the effective substance of Fe(NO3)3·9H2O is Fe2O3, and the effective substance of Ni(NO3)2·6H2O is NiO. The total molar amount of Mo and Fe in the catalyst is calculated to be 2.83mmol (i.e. the total mass of MoO3 and Fe2O3 accounts for 12wt% of the catalyst mass), and the mass of NiO accounts for 4wt% of the catalyst mass, where the molar ratio of Mo to Fe is 36:1; the mass of carrier A is 3g. Finally, the required 0.487g (NH4)6Mo7O 24 ·4H2O, 0.0309g Fe(NO3)3·9H2O, 0.487g Ni(NO3)2·6H2O.

[0077] 0.487g(NH4)6Mo7O 24·4H2O, 0.0309g Fe(NO3)3·9H2O, and 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion, ferric nitrate dispersion, and nickel nitrate dispersion, respectively; 3g of carrier A was first impregnated in 3mL of ammonium molybdate dispersion, and dried at room temperature for 12h after impregnation, and then the dried sample was impregnated in 3mL of ferric nitrate dispersion, and dried at room temperature for 12h, and finally the obtained sample was impregnated in 3mL of nickel nitrate dispersion, and dried at room temperature for 12h after impregnation, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst NiMoFe / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed. The order of immersing the support in the ammonium molybdate dispersion and the ferric nitrate dispersion may be changed.

[0078] Embodiment 4:

[0079] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0080] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0081] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24The effective substance of Fe(NO3)3·9H2O is MoO3, the effective substance of Fe(NO3)3·9H2O is Fe2O3, and the effective substance of Ni(NO3)2·6H2O is NiO. The total molar amount of Mo and Fe in the catalyst is calculated to be 2.83mmol (i.e. the total mass of MoO3 and Fe2O3 accounts for 12wt% of the catalyst mass), and the mass of NiO accounts for 4wt% of the catalyst mass, where the molar ratio of Mo to Fe is 24:1; the mass of carrier A is 3g. Finally, the required 0.481g (NH4)6Mo7O 24 ·4H2O, 0.0459g Fe(NO3)3·9H2O, 0.487g Ni(NO3)2·6H2O.

[0082] 0.481g(NH4)6Mo7O 24 ·4H2O, 0.0459g Fe(NO3)3·9H2O, and 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion, ferric nitrate dispersion, and nickel nitrate dispersion, respectively; 3g of carrier A was first impregnated in 3mL of ammonium molybdate dispersion, and dried at room temperature for 12h after impregnation, and then the dried sample was impregnated in 3mL of ferric nitrate dispersion, and dried at room temperature for 12h, and finally the obtained sample was impregnated in 3mL of nickel nitrate dispersion, and dried at room temperature for 12h after impregnation, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst NiMoFe / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed. The order of immersing the support in the ammonium molybdate dispersion and the ferric nitrate dispersion can be changed.

[0083] Embodiment 5:

[0084] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0085] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0086] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24 The effective substance of Fe(NO3)3·4H2O is MoO3, the effective substance of Fe(NO3)3·9H2O is Fe2O3, and the effective substance of Ni(NO3)2·6H2O is NiO. The total molar amount of Mo and Fe in the catalyst is calculated to be 2.83mmol (i.e. the total mass of MoO3 and Fe2O3 accounts for 12wt% of the catalyst mass), and the mass of NiO accounts for 4wt% of the catalyst mass, where the molar ratio of Mo to Fe is 12:1; the mass of carrier A is 3g. Finally, the required 0.462g (NH4)6Mo7O 24 ·4H2O, 0.088g Fe(NO3)3·9H2O, 0.487g Ni(NO3)2·6H2O.

[0087] 0.462g(NH4)6Mo7O 24 ·4H2O, 0.088g Fe(NO3)3·9H2O, and 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion, ferric nitrate dispersion, and nickel nitrate dispersion, respectively; 3g of carrier A was first impregnated in 3mL of ammonium molybdate dispersion, and dried at room temperature for 12h after impregnation, and then the dried sample was impregnated in 3mL of ferric nitrate dispersion, and dried at room temperature for 12h, and finally the obtained sample was impregnated in 3mL of nickel nitrate dispersion, and dried at room temperature for 12h after impregnation, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst NiMoFe / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed. The order of immersing the support in the ammonium molybdate dispersion and the ferric nitrate dispersion can be changed.

[0088] Comparative Example 1:

[0089] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0090] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0091] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24 The effective substance of Ni(NO3)2·6H2O is MoO3, and the effective substance of Ni(NO3)2·6H2O is NiO. The molar amount of Mo loaded in the catalyst is calculated to be 2.83mmol (i.e. the total mass of loaded MoO3 accounts for 12wt% of the mass of the catalyst), and the mass of loaded NiO accounts for 4wt% of the mass of the catalyst; the mass of carrier A is 3g. Finally, the required 0.501g (NH4)6Mo7O 24 ·4H2O, 0.487g Ni(NO3)2·6H2O.

[0092] 0.501g(NH4)6Mo7O 24 ·4H2O, 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion and nickel nitrate dispersion respectively; 3g of carrier A was first impregnated in 3mL of ammonium molybdate dispersion, and then dried at room temperature for 12h, and then the dried sample was impregnated in 3mL of nickel nitrate dispersion, and then dried at room temperature for 12h, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst NiMo / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed.

[0093] Comparative Example 2:

[0094] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0095] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0096] Carrier A was used for subsequent experiments: First, it should be made clear that the effective substance of Fe(NO3)3·9H2O is Fe2O3, and the effective substance of Ni(NO3)2·6H2O is NiO. The total mass of Fe2O3 loaded in the catalyst accounts for 12wt% of the catalyst mass, and the mass of NiO loaded accounts for 4wt% of the catalyst mass; the mass of carrier A is 3g. Finally, it was calculated that 2.07g of Fe(NO3)3·9H2O and 0.487g of Ni(NO3)2·6H2O were required.

[0097] 2.07g Fe(NO3)3·9H2O and 0.487g Ni(NO3)2·6H2O were dissolved in 3mL of deionized water to obtain ferric nitrate dispersion and nickel nitrate dispersion respectively; 3g of carrier A was first impregnated in 3mL of ferric nitrate dispersion, and then dried at room temperature for 12h, and finally the obtained sample was impregnated in 3mL of nickel nitrate dispersion, and then the sample was dried at room temperature for 12h, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst FeNi / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed.

[0098] Comparative Example 3:

[0099] (1) Under magnetic stirring, 8.16 g of Al[OCH(CH3)2]3 was dissolved in a three-necked flask containing 40.0 mL of EtOH and stirred at 800 rpm for 4 h. Then, 3.2 mL of concentrated HNO3 was added dropwise within 10 min (dropwise to avoid condensation). After the temperature dropped to room temperature, 20 mL of EtOH dispersion containing 4.0 g of P123 was added dropwise to the flask within 5 min. The mixture was then dried at 120°C for 48 h. After drying, the mixture was calcined at 550°C for 4 h (heating rate of 1°C / min) to completely remove the structure directing agent P123. The obtained product was recorded as carrier A.

[0100] (2) Take 0.5 g of the carrier A obtained in step (1) and store it in a tube, affix a label, indicate that it is the carrier, content, and mass, and use it for pre-impregnation; put the carrier A sample (0.5 g) for pre-impregnation in a sample tube, add deionized water dropwise, and accurately record how many milliliters of water are added to achieve an equal volume impregnation state. As a result, it is calculated that the deionized water used is 3 mL; the 3 mL of water obtained is the amount of water required for the carrier A to reach an equal volume impregnation state.

[0101] Based on carrier A, subsequent experiments were performed: First, it should be made clear that (NH4)6Mo7O 24 The effective substance of Fe(NO3)3·9H2O is MoO3, and the effective substance of Fe(NO3)3·9H2O is Fe2O3. The total molar amount of Mo and Fe in the catalyst is calculated to be 2.83mmol (i.e. the total mass of MoO3 and Fe2O3 accounts for 12wt% of the catalyst mass), where the molar ratio of Mo to Fe is 36:1; the mass of carrier A is 3g. Finally, the required 0.487g (NH4)6Mo7O 24 ·4H2O, 0.0309g Fe(NO3)3·9H2O.

[0102] 0.487g(NH4)6Mo7O 24 ·4H2O, 0.0309g Fe(NO3)3·9H2O were dissolved in 3mL of deionized water to obtain ammonium molybdate dispersion and ferric nitrate dispersion respectively; 3g of carrier A was first immersed in 3mL of ammonium molybdate dispersion, and then dried at room temperature for 12h, and then the dried sample was immersed in 3mL of ferric nitrate dispersion, and then dried at room temperature for 12h, and then placed in an oven at 120℃ for 12h, and finally placed in a muffle furnace for calcination at 550℃ for 4h (heating rate of 1℃ / min) to obtain a solid catalyst MoFe / Al2O3. Among them, 3mL of dispersion can just soak 3g of carrier, and no excess dispersion flows out, so that all metal salts are adsorbed.

[0103] Embodiment 6:

[0104] The catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were characterized. The XRD spectrum of the NiMoFe / Al2O3 catalyst is shown in FIG. Figure 1 As shown, a is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 144:1 prepared in Example 1; b is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 72:1 prepared in Example 2; c is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 36:1 prepared in Example 3; d is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 24:1 prepared in Example 4; and e is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 12:1 prepared in Example 5. As can be seen from the figure, as the molar ratio of Mo to Fe changes, the diffraction peak does not change significantly, indicating that the change in the molar ratio of Mo to Fe does not change the structure of the catalyst, eliminating the influence of the structure on the catalyst.

[0105] Embodiment 7:

[0106] The catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to hydrogenation performance evaluation. A dodecane dispersion containing 500 ppm of 4,6-dimethyldibenzothiophene (4,6-DMDBT) was used as the reaction raw material. The reaction conditions were: reaction temperature 340°C, hydrogen partial pressure 4 MPa, liquid hourly space velocity 2.5 to 100 h -1 , hydrogen oil volume ratio 200:1. 4,6-DMDBTHDS conversion rate is as follows Figure 2 and Figure 3 shown.

[0107] Figure 2 In the figure, a is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 144:1 prepared in Example 1; b is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 72:1 prepared in Example 2; c is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 36:1 prepared in Example 3; d is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 24:1 prepared in Example 4; e is NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 12:1 prepared in Example 5. As can be seen from the figure, as the molar ratio of Mo to Fe continues to decrease, the conversion rate of 4,6-DMDBT HDS gradually increases, reaching a maximum value when the molar ratio of Mo to Fe is 36:1, and then the molar ratio of Mo to Fe continues to decrease, and the catalytic activity decreases, indicating that the optimal conversion rate has been achieved when the molar ratio of Mo to Fe is 36:1.

[0108] Figure 3In the figure, a uses NiMoFe / Al2O3 with a molar ratio of Mo to Fe of 36:1 prepared in Example 3; b uses NiMo / Al2O3 prepared in Comparative Example 1, c uses FeNi / Al2O3 prepared in Comparative Example 2, and d uses MoFe / Al2O3 prepared in Comparative Example 3. It can be seen from the figure that at a liquid hourly space velocity of 10, compared with the active components of nickel-molybdenum, iron-nickel and molybdenum-iron combination, the nickel-molybdenum-iron ternary active component can still maintain a higher activity at a higher flow rate.

[0109] The present invention provides a diesel NiMoFe / Al2O3 hydrodesulfurization catalyst and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A diesel NiMoFe / Al2O3 hydrodesulfurization catalyst, characterized in that: The hydrodesulfurization catalyst comprises an Al2O3 carrier and an active component loaded on the Al2O3 carrier; Wherein, the active ingredients are composed of molybdenum oxide, iron oxide and nickel oxide; The total mass of the molybdenum oxide and the iron oxide accounts for 8% to 13% of the total mass of the catalyst; the mass of the nickel oxide accounts for 4% of the total mass of the catalyst; the molar ratio of molybdenum to iron is 12 to 144:1; The molybdenum oxide is molybdenum trioxide; the iron oxide is ferric oxide; and the nickel oxide is nickel oxide.

2. The method for preparing the diesel NiMoFe / Al2O3 hydrodesulfurization catalyst according to claim 1, characterized in that: The steps include: (1) dissolving triisopropoxyaluminum in a first solvent and stirring, then adding an acid to assist dissolution, then adding a structure directing agent and mixing, then drying and first calcining to obtain a carrier; (2) dispersing a molybdenum salt, an iron salt, and a nickel salt in a second solvent to obtain a molybdenum salt dispersion, an iron salt dispersion, and a nickel salt dispersion, respectively; (3) impregnating the support obtained in step (1) with a molybdenum salt dispersion, and drying after impregnation; and then impregnating the support with an iron salt dispersion, and drying after impregnation; Finally, the nickel salt dispersion is impregnated, and then dried; or, The carrier obtained in step (1) is impregnated with an iron salt dispersion, and then dried; then impregnated with a molybdenum salt dispersion, and then dried; and finally impregnated with a nickel salt dispersion, and then dried; (4) drying the product obtained in step (3) and performing a second calcination to obtain a NiMoFe / Al2O3 hydrodesulfurization catalyst.

3. The preparation method according to claim 2, characterized in that: In step (1), the first solvent is any one or a combination of ethanol and water; the stirring time is 2 to 6 hours; the acid is any one or a combination of nitric acid, hydroiodic acid, hydrobromic acid, hydrochloric acid and sulfuric acid; the structure directing agent is any one or a combination of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; the mass ratio of triisopropoxy aluminum to the structure directing agent is 2.0 to 2.5:1; In step (1), the first calcination is to raise the temperature from room temperature to 550-560° C. at a heating rate of 1-5° C. / min, and calcine at 550-560° C. for 2-6 hours.

4. The preparation method according to claim 2, characterized in that: In step (2), the molybdenum salt is ammonium heptamolybdate tetrahydrate; the iron salt is ferric nitrate nonahydrate; the nickel salt is nickel nitrate hexahydrate; and the second solvent is water.

5. The preparation method according to claim 4, characterized in that: In step (2), the ammonium heptamolybdate tetrahydrate is calculated as molybdenum trioxide, the ferric nitrate nonahydrate is calculated as ferric oxide, and the total mass of the molybdenum trioxide and the ferric oxide accounts for 8% to 13% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst; the molar ratio of molybdenum in the ammonium heptamolybdate tetrahydrate to iron in the ferric nitrate nonahydrate is 12 to 144:1; the nickel nitrate hexahydrate is calculated as nickel oxide, and the nickel oxide accounts for 4% of the mass of the NiMoFe / Al2O3 hydrodesulfurization catalyst.

6. The preparation method according to claim 2, characterized in that: In step (3), the mass volume ratio of the carrier to the molybdenum salt dispersion is 1g:1.0~1.2mL; the mass volume ratio of the carrier to the iron salt dispersion is 1g:1.0~1.2mL; the mass volume ratio of the carrier to the nickel salt dispersion is 1g:1.0~1.2mL.

7. The preparation method according to claim 2, characterized in that: In step (4), the second calcination is performed by raising the temperature from room temperature to 550-560° C. at a heating rate of 1-5° C. / min, and calcining at 550-560° C. for 2-6 hours.

8. The diesel NiMoFe / Al2O3 hydrodesulfurization catalyst prepared by the preparation method according to any one of claims 2 to 7.

9. Use of the diesel NiMoFe / Al2O3 hydrodesulfurization catalyst according to claim 8 in the desulfurization of petroleum fractions.

10. The use according to claim 9, characterized in that: Using the diesel NiMoFe / Al2O3 hydrodesulfurization catalyst as claimed in claim 8 as a catalyst, catalyzing the hydrodesulfurization reaction of sulfur-containing petroleum fractions; The hydrodesulfurization reaction has a reaction temperature of 340-360°C, a hydrogen partial pressure of 4-6 MPa, and a liquid hourly space velocity of 2.5-100 h -1 , hydrogen-oil volume ratio 200:1.

Citation Information

Patent Citations

  • Catalyst used for hydrodesulphurization of coke-oven gas and preparation method thereof

    CN101797513A

  • Low-loading-quantity coke oven gas hydrogen desulfurization catalyst as well as preparation method and application thereof

    CN108855116A

  • Hydrodesulfurization catalyst and preparation method and application thereof

    CN111298800A